Estudio de los determinantes moleculares involucrados en la traducción de los ARN mensajeros de arenavirus - Foscaldi, Sabrina Andrea (2016)
The genome of Tacaribe virus (TCRV), prototype of the New World\narenaviruses, encodes four proteins which are expressed from subgenomic\nmessenger RNAs (mRNAs). These mRNAs contain Cap structure at the 5? end,\nand lack a 3? poly(A) tail, exhibiting a 3? untranslated region (UTR) predicted to\nform a stable secondary hairpin structure with a suspected role in translation.\nTo analyze the contribution of non-coding sequences to TCRV mRNAs\ntranslation, we generated a synthetic transcript mimicking the TCRV\nNucleoprotein (NP) mRNA, which contains the Firefly Luciferase (FLUC) open\nreading frame. Mutant mRNAs were designed to carry modifications in either\nthe 5? or the 3? UTR. Translation from these virus-like mRNAs in transfected\ncells was evidenced by FLUC activity, along with determination of mRNA\nstability by qPCR. Taken together, the data suggested that the predicted hairpin\nstability at the 3?UTR and/or its G/C content play a modulatory role in\ntranslation. In addition, both the sequence neighboring the stop codon in the 3?\nUTR, and the 5' UTR were found to contain sequence or structure elements\nwhich stimulate translation. It was also observed that the presence of NP or\nother viral proteins do not affect translation, and that this process requires the\neukaryotic translation factor eIF4GI. Also, this study succeeded in developing a\nreverse genetic system that directs the generation of recombinant TCRV, a\nvaluable tool that will allow performing mechanistic studies in the context of a\nviral infection.